USP43 promotes tumorigenesis through regulating cell cycle and EMT in breast cancer - Lin, Fei (Int J Clin Exp Pathol, 2017)
USP is one protease family of deubiquitylating enzyme (DUB). It removes ubiquitin from substrate and stabilizes the substrate. Here, we scanned several novel deubiquitinate enzymes in breast cancer tissue samples, and found that USP43 was up-regulated in breast cancer and closely relationship with metastasis, tumor size and a poor prognosis. Consequently, CCK-8 assay and colony formation assay were used to assess the function of USP43 in cell proliferation. Moreover, cell apoptosis assay and cell cycle assay revealed that USP43 facilitated cells G(1)/S phase transition, but had slightly influence in cell apoptosis. EMT is a current event in breast cancer; the cells which happened have strong metastasis ability. We next detected whether USP43 regulated EMT, our results demonstrated that USP43 promoted EMT through regulated snail, thereby facilitated breast cancer cells metastasis. In brief, our works showed a novel mechanism of USP43 in facilitating breast cancer cells proliferation and metastasis. In addition, USP43 might be a novel therapeutic target for breast carcinoma.